Living Law sebagai Instrumen Kebijakan Kriminal dalam KUHP Baru Indonesia - Zul Khaidir Kadir (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to assess the position of living law as a criminal policy tool, examine whether such recognition results in substantive integration or instrumentalization of culture, and assess its implications for the rule of law and the criminal justice system. The research method used is normative legal research with a legislative approach and a conceptual approach. The results confirm that Article 2 of the New Criminal Code expands the basis of criminal justice legitimacy without adopting the internal community mechanisms that support customary norms, so that social norms shift into material managed by law enforcement institutions. This configuration widens discretion, disrupts predictability, and opens up fragmentation of criminal justice standards between communities, especially for parties in subordinate social relations, while maintaining the centralization of state authority over coercion.